Optimizing Whole Brain Radiotherapy Treatment and Dose for Patients With Brain Metastases From Small Cell Lung Cancer - Li, Hanming; Li, Wang; Qi, Chao; Zhou, Lu; Wen, Fengyun; Qu, Yanli; Yu, Hong (Frontiers in Oncology, 2021)
Purpose: This study aimed to evaluate the survival outcomes of whole brain radiotherapy (WBRT) compared to whole brain radiotherapy plus local radiation boost (WBRT + boost), and further identify whether higher biologically effective dose (BED) of WBRT + boost translates into a survival benefit in small cell lung cancer (SCLC) patients with brain metastasis (BM). Methods: SCLC patients with BM from January 1, 2012, to December 31, 2019, were retrospectively analyzed. Overall survival (OS) and intracranial progression-free survival (iPFS) were evaluated by the Kaplan-Meier method and compared by the log-rank test. Univariate and multivariate regression analyses of prognostic factors for OS were performed using Cox proportional hazards regression models. The cut-off value of BED was determined by the receiver operating characteristic (ROC) curve analysis. Results: Among the 180 eligible patients, 82 received WBRT + boost, 98 received WBRT. Both OS and iPFS in the WBRT + boost group were significantly superior to those in the WBRT group (median overall survival (OS): 20 vs. 14 months, P = 0.011; median intracranial progression-free survival (iPFS): 16 vs. 10 months, P = 0.003). At a cut-off value of 58.35Gy in the WBRT + boost group, 52 for the high-BED (> 58.35Gy) group, 30 for the low-BED (≤ 58.35Gy) group. High BED was significantly associated with improved OS and iPFS compared with low BED in the WBRT + boost group (median OS: 23 vs. 17 months, P = 0.002; median iPFS: 17 vs. 10 months, P = 0.002). Conclusions: Compared with WBRT alone, WBRT + boost improved OS and iPFS in SCLC patients with BM. High BED (> 58.35Gy) for WBRT + boost may be a reasonable consideration for SCLC patients with BM.